KEEFEKTIFAN MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR TEMATIK INTEGRATIF PESERTA DIDIK KELAS IV MII - Fatikhin, Muhammad Kholisul; Kristanto, M. (Universitas Pendidikan Indonesia, 2014)
The problems revealed in this study is whether the model of Quantum Teaching effectively to improve the learning outcomes of the thematic integrative fourth grade students? The population in this experimental study is a fourth grade student MII Simbang Wetan Pekalongan the number of 40 students. Samples taken is grade IV were 40 and divided into two classes, namely class IVA and IVB class each totaling 20 learners by using simple random sampling technique. The results showed that learners were subjected to a model of Quantum Teaching gain value - average 75.55, and the number of students who complete 20 to 95% the percentage of completeness. While the students who received the lecture method to obtain an average 70.45, and the number of students who complete 20 to 70% the percentage of completeness. Learning outcomes of students who got a better model of Quantum Teaching of students who received lecture method. This is in line with the learning outcomes in terms of cognitive and psychomotor aspects as a supporter. The result is students to be more active in learning activities. Besides, the students are also more freedom to exclude ideas - ideas in learning. Keywords: effectiveness, models of quantum teaching, learning outcomes of students.